UMP, TERAJU enhance bumiputera development sustainability in agricultural projects - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 23 October 2021 – Universiti Malaysia Pahang (UMP) and Bumiputera Agenda Steering Unit (TERAJU) signed a memorandum of agreement (MoA) which will open up opportunities for small- and medium-enterprise entrepreneurs (B40 group) to produce agricultural products (chilli and eggplant) for local market through the Bumiputera Entrepreneur Development Fund Programme (DPUB).